The relationship self-regulated learning strategies and test anxiety among INSTED IIUM students - Sri Nurul Milla (Institute of Education, International Islamic University Malaysia, 2012)
The main purpose of this study is to determine whether students' use of self-regulated learning strategies has any significant relationship with their level of test-anxiety. Besides, this study aimed to assess the current status of INSTED students' level of test anxiety, to evaluate variations of INSTED IIUM students' level of test anxiety based on their age, gender, and degree programme, and to assess the extent of use of self-regulated learning strategies among INSTED students. The questionnaire adapted from the Spielberger (1988) Test Anxiety Inventory and Magno (2010) Academic Self-Regulated Learning Scale was distributed to 280 INSTED IIUM students. The data were analyzed using the descriptive, independent t-test analysis, one-way ANOVAs, post-hoc test, and Pearson product-moment correlation. The major finding of the study revealed that: most of the INSTED IIUM students experience a high level of test anxiety; there was a significant mean difference in INSTED IIUM students' level of test anxiety between the genders, age groups, and degree programmes; INSTED IIUM students' level of test-anxiety was not significantly related to their use of self-regulated learning strategies in general; however, it was significantly correlated with the use of memory strategy and environmental structuring.